Graffiti and the Discursive Construction of Fitness in Gyms - Echitchi, Raymond (Respectus Philologicus, 2022)
This paper is an attempt to add knowledge to scholarship in a field that has attracted less attention from researchers. It presents a study of graffiti found on a board located inside a gym in Madrid that was carried out in order to get a grasp of the functions of the graffiti and gain an insight into discursive practices in gyms. Data analysis focused on texts while overlooking the graffiti’s non-verbal features and was carried out following Fairclough’s (2004, 2013) approach, which emphasizes the study of language as a social practice and encourages a three-fold analysis of discourse that includes action, representation and identification. The study revealed that social agents attempted to act and interact directly or indirectly with fellow gym-goers through graffiti.